Capture coefficients of free excitons by shallow acceptors and donors in gallium arsenide - Glinchuk, K.D.; Litovchenko, N.M.; Strilchuk, O.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
An analysis of the 4.2 K exciton luminescence spectra of semi-insulating GaAs crystals with different concentrations of shallow acceptors (С) and donors (Si) is given. As a result, the 4.2 K capture coefficients of free excitons by shallow neutral acceptors [bA₀X = (4 ± 2) 10⁻⁸ cm³/s] and donors [bD₀X= (1.5 ± 0.8) 10⁻⁷ cm³/s] are found and also an estimate of the capture coefficient of free excitons by ionized shallow donors was made .